Respuesta :

Answer:

z = 23/12

Step-by-step explanation:

13(z+4)−6=23(5−z)

Distribute

13z + 52 -6 = 115 - 23z

Combine like term

13z+46 = 115 -23z

Add 23z to each side

13z+23z+46 = 115-23z+23z

36z +46 = 115

Subtract 46 from each side

36z+46-46 = 115-46

36z=69

Divide each side by 36

36z/36 = 69/36

z = 23/12

Answer:

[tex]z=\frac{23}{12}[/tex]

Step-by-step explanation:

  • [tex]13(z+4)-6=23(5-z)\\13z+52-6=115-23z\\13z+46=115-23z\\13z+(23z)+46-(46)=115-(46)+23z-(23z)\\36z=69\\z=69\div 36\\z=\frac{69}{36}=\frac{23}{12}[/tex] I'd appreciate a brainliest
ACCESS MORE